The Scientific Discourse of Contemporary Humanities. Towards Postmodern De/Normalization (?) - Rejter, Artur (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
This article addresses the latest stage of transformations in Polish scientific discourse, the origins of which are commonly traced back to the 16th century in relation to Polish culture. The paper provides a synthetic and report-like overview, offering several key insights regarding the examined area of communication: 1. Changes in the discourse in contemporary humanities, influenced by the intellectual aura of postmodernism, pertain to certain areas of scientific reflection. 2. Science reflects the transformations in cultural and social nature, thus scientific discourse absorbs the characteristics of the world it describes. 3. Revaluations within scientific discourse serve as a certain signal of its denormalisation, although this process does not encompass the entirety of scientific communication but rather signifies cracks and shifts that emerge in the proposed and normative understanding of discourse. 4. Transformations within scientific discourse should not be regarded as a crisis, but rather as manifestations of certain qualities and general tendencies in culture that may bring new and surprising effects in the future. 5. The transformations of scientific discourse are also influenced by the field in which it operates. The specific nature of humanities sciences, situated in a particular way in relation to other branches of knowledge, should be taken into account. 6. Despite changes in the scope of scientific discourse, many of its characteristics remain relevant. 7. Scientific discourse should not be regarded as monolithic; on the contrary, it is a complex, multidimensional quality dependent on various aspects. 8. The specificity of scientific discourse as one of the areas of communication becomes more graspable when examined from a certain distance. Therefore, a historical perspective on the issue proves fortunate for the proposed conclusions.